Technological achievement in the food industry in Malaysia - Rahmat, Suharni; Abdul Hamid, Mohd Syaiful Rizal; Chew, Boon Cheong (Rynnye Lyan Resources, 2022)
Issues pertaining to food sustainability have long been debated in developing countries. Food sustainability practices benefit the environment, societies and economies, yet in Malaysia food production and management are still lagging in sustainability practices. The food industry needs to explore new methods in food production because of population increase, peoples’ lifestyle, demand for healthy foods, and environmental concerns. For this reason, this review paper discussed technological achievements in the food industry to help food producers improve production. It is crucial for Malaysia to ensure sustainability in food production technology in the 12th Economic Planning Unit (EPU) projection for 2021-2025. The EPU aims to restructure and empower the existing industry. This paper discussed the food technology sub-sector focusing on agriculture and livestock in Malaysia. This focus hopes to boost existing government strategies and improve food producers’ business performance following the EPU. Here, this paper highlights the government’s involvement in technology application to help farmers’ access affordable technology via research assistance from the government.